Efficacy of finafloxacin in a murine model of inhalational glanders - Barnes, Kay B.; Bayliss, Marc; Davies, Carwyn; Richards, Mark I.; Laws, Thomas R.; Vente, Andreas; Harding, Sarah V. (Frontiers in Microbiology, 2022)
Burkholderia mallei, the causative agent of glanders, is primarily a disease of equines, although it can also infect humans and is listed by the U.S. Centers for Disease Control and Prevention as a category B biological agent. There is limited literature available related to the treatment of glanders in humans, and it is therefore recommended that cases should be treated with the same therapies as used for melioidosis, which for prophylaxis, is co-trimoxazole (trimethoprim/sulfamethoxazole) or co-amoxiclav (amoxicillin/clavulanic acid). In this study, the fluoroquinolone finafloxacin was compared to co-trimoxazole as a post-exposure prophylactic in a murine model of inhalational glanders. BALB/c mice were exposed to an aerosol of B. mallei followed by treatment with co-trimoxazole or finafloxacin initiated at 24 hours post-challenge and continued for 14 days. Finafloxacin demonstrated a high level of protection and was more effective than co-trimoxazole in controlling bacterial load within tissues and demonstrating clearance in the liver, lung and spleen following 14 days of therapy. In summary, finafloxacin should be considered as a promising alternative treatment following exposure to B. mallei.